Respuesta :

Answer:

1 - Copy and complete this table for y = 2x

x = -3 | y = -6

x = -2 | y = -4

x = -1 | y = -2

x = 0 | y = 0

x = 1 | y = 2

x = 2 | y = 4

x = 3 | y = 6

2 - Copy and complete this table for y = 2x - 3

x = -2 | y = -7

x = -1 | y = -5

x = 0 | y = -3

x = 1 | y = -1

x = 2 | y = 1

x = 3 | y = 3

x = 4 | y = 5

x = 5 | y = 7

y=2x

The way to solve this is plugging in your above x value in for x into the equation y=2x and solving for y.

Example:

y=2x

^You want to find x=-3

y= 2(-3)

y= -6

Your answers:

-6, -2, 0, 4, 6

y=2x -3

Same concept here as above. You are solving for y when you plug in the given x value into the equation.

Your answers:

-5, -3, -1, 3, 5